Pasture and animal responses of Coastcross swards grazed by sheep under continuous stocking - Carnevalli, Roberta Aparecida; Silva, Sila Carneiro da; Carvalho, Carlos Augusto Brandão de; Sbrissia, André Fischer; Fagundes, Jailson Lara; Pinto, Luiz Felipe de Moura; Pedreira, Carlos Guilherme Silveira (Pesquisa Agropecuaria Brasileira, 2001)
Pasture and animal responses of Coastcross (Cynodon spp.) swards were evaluated under four steady state conditions (sward surface heights of 5, 10, 15 and 20 cm), established by sheep under continuous stocking and variable stocking rate from August/98 to April/99. Sward surface heights were allocated to experimental units randomly, according to a complete randomized block design, with four replications. The variables evaluated were herbage nutritive value, morphological composition of the herbage as grazed hand sample and of the sward, herbage accumulation rate and animal performance. All swards presented high nutritive value of the grazed herbage during spring and summer, with the best values observed for the sward height of 5 cm. Herbage accumulation rates were highest in summer, which generated higher dry matter availability and animal performance.